The waiting room. - Chua, Xin Jie. (2012)
The act of waiting is to stay where one is or delay action until a particular time or until something else happens. Contrary to its apparent implication, The Waiting Room is an installation that aims to stimulate action and reaction within those in wait, to cultivate a sense of urgency to take action in lieu of waiting for an indefinite time to occur.